PENGARUH SIKAP MODERASI DAN PENGETAHUAN AGAMA ISLAM TERHADAP WAWASAN KEBANGSAAN: PENGARUH SIKAP MODERASI DAN PENGETAHUAN AGAMA ISLAM TERHADAP WAWASAN KEBANGSAAN - Hardin, Suhardin Din (AL-WIJDÃƒÂN: Journal of Islamic Education Studies, 2019)
ABSTRACT The objective of this research to find out the effect of moderation attitude with Islamic religion knowledge for the nation view. The research was conducted in SMA Negeri 5 Depok using 2X2 design involving 60 students chosen by using purposive random sampling. The data analysis and interpretation indicated that: 1. There is difference in students' high moderation attitude between students' low moderation attitude, 2. There is difference in students' high Islamic religion knowledge between students' low Islamic religion knowledge, 3. There is not interaction between of moderation attitude and Islamic relegion knowledge against the nation view, 4. The students high moderation attitude with high Islamic relegion knowledge not diffrence than students low moderation attitude high Islamic relegion knowledge, 4.The students high moderation attitude and low Islamic relegion knowledge not diffrence than The students low moderation attitude and low Islamic relegion knowledge. Key Words : moderation attitude, Islamic relegion knowledge, nation view.